Identification of a Splenic Marginal Zone Lymphoma Signature: Preliminary Findings With Diagnostic Potential - Robinson, Jacob E.; Greiner, Timothy C.; Bouska, Alyssa C.; Iqbal, Javeed; Cutucache, Christine E. (Frontiers in Oncology, 2020)
Splenic marginal zone lymphoma (SMZL) is a rare, indolent non-Hodgkin’s lymphoma that affects 0.13 per 100,000 persons annually. Overall survival of SMZL is estimated to reach 8 to 11 years in most cases, but up to 30% of SMZL cases develop aggressive presentations resulting in greatly diminished time of survival. SMZL presents with a very heterogeneous molecular profile, making diagnosis problematic and accurate prognosis even less likely. The study herein has identified a potential diagnostic gene expression signature with highly specific predictive utility, coined the SMZL-specific Gene Expression Signature (SSGES). Additionally, five of the most impactful markers identified within the SSGES were selected for a 5-protein panel, for further evaluation among control and SMZL patient samples. These markers included EME2, ERCC5, SETBP1, USP24, and ZBTB32. When compared with control spleen and other B-cell lymphoma subtypes, significantly higher expression was noticed in SMZL samples when stained for EME2 and USP24. Additionally, ERCC5, SETBP1, USP24, ZBTB32 staining displayed indications of prognostic value for SMZL patients. Delineation of the SSGES offers a unique SMZL signature that could provide diagnostic utility for a malignancy that has historically been difficult to identify, and the 5-marker protein panel provides additional support for such findings. These results should be further investigated and validated in subsequent molecular investigations of SMZL so it may be potentially incorporated into standard oncology practice for improving the understanding and outlook for SMZL patients.